The GALAH survey: second data release - Buder, Sven (Monthly notices of the Royal Astronomical Society, 2018)
Abstract: The Galactic Archaeology with HERMES (GALAH) survey is a large-scale stellar spectro-scopic survey of the Milky Way, designed to deliver complementary chemical information to alarge number of stars covered by the Gaia mission. We present the GALAH second public datarelease (GALAH DR2) containing 342 682 stars. For these stars, the GALAH collaboration provides stellar parameters and abundances for up to 23 elements to the community. Here wepresent the target selection, observation, data reduction, and detailed explanation of how thespectra were analysed to estimate stellar parameters and element abundances. For the stellaranalysis, we have used a multistep approach. We use the physics-driven spectrum synthesis of Spectroscopy Made Easy(SME) to derive stellar labels (Teff,logg, [Fe/H], [X/Fe],vmic,vsini,AKS) for a representative training set of stars. This information is then propagated to the wholesample with the data-driven method of The Cannon. Special care has been exercised in thespectral synthesis to only consider spectral lines that have reliable atomic input data and arelittle affected by blending lines. Departures from local thermodynamic equilibrium (LTE) areconsidered for several key elements, including Li, O, Na, Mg, Al, Si, and Fe, using 1DMARCSstellar atmosphere models. Validation tests including repeat observations, Gaia benchmark stars, open and globular clusters, and K2 asteroseismic targets lend confidence to our methodsand results. Combining the GALAH DR2 catalogue with the kinematic information from Gaia will enable a wide range of Galactic Archaeology studies, with unprecedented detail,dimensionality, and scope.
Gesehen am 22.10.2019